Pemanfaatan Aplikasi Photomath pada Pembelajaran Matematika: Systematic Literature Review - Thania Wulandari; Yahfizam (UNIVERSITAS SERAMBI MEKKAH, 2024)
As technology develops, the application of software/application can be one of the alternatives in learning mathematics. This research aims to identify the use of photomath application in mathematics learning. This scientific article was prepared using the Systematic Literature Review (SLR) method. SLR is a method in order to identify, review, and conclude several studies related to the theme discussed. The articles reviewed were 72 articles related to the utilisation of applications in learning mathematics, which came from the google schoolar database for the last 10 years (2013-2023). Based on the literature review conducted, it is found that the use of photomath applications in mathematics learning can make it easier for students to access and understand materials related to mathematics, especially matrix materials, because this application provides more interesting and interactive content and can improve students' mathematical communication skills.